Finntopia what we can learn from the world's happiest country - Dorling, Daniel 1968-; Koljonen, Annika (Agenda Publishing, 2023)
The 2020 World Happiness Report ranked Finland, for the third year running, as the world's happiest country. The 'Nordic Model' has long been touted as the aspiration for social and public policy in Europe and North America, but what is it about Finland that makes the country so successful and seemingly such a great place to live? Is it simply the level of government spending on health, education and welfare? Is it that Finland has one of the lowest rates of social inequality and childhood poverty, and highest levels of literacy and education? Finland clearly has problems of its own - for example, a high level of gun ownership and high rates of suicide - which can make Finns skeptical of their ranking, but its consistently high performance across a range of well-being indicators does raise fascinating questions. In the quest for the best of all possible societies, Danny Dorling and Annika Koljonen explore what we might learn from Finnish success